Characterization of skin aging-associated secreted proteins (SAASP) produced by dermal fibroblasts isolated from intrinsically aged human skin - Waldera-Lupa, Daniel Michael; Kalfalah, Faiza; Safferling, Kai; Boukamp, Petra; Poschmann, Gereon; Volpi, Elena; Götz-Rösch, Christine; Bernerd, Francoise; Haag, Laura; Huebenthal, Ulrike; Fritsche, Ellen; Boege, Fritz; et al. (The journal of investigative dermatology, 2015)
Most molecular hallmarks of cellular senescence have been identified in studies of cells aged in vitro by driving them into replicative or stress-induced senescence. Comparatively, less is known about the characteristic features of cells that have aged in vivo. Here we provide a systematic molecular analysis of normal human dermal fibroblasts (NHDFs) that were isolated from intrinsically aged human skin of young versus middle aged versus old donors. Intrinsically aged NHDFs in culture exhibited more frequently nuclear foci positive for p53 binding protein 1 and promyelocytic leukemia protein reminiscent of ‘DNA segments with chromatin alterations reinforcing senescence (DNA-SCARS)’. Formation of such foci was neither accompanied by increased DNA double strand breaks, nor decreased cell viability, nor telomere shortening. However, it was associated with the development of a secretory phenotype, indicating incipient cell senescence. By quantitative analysis of the entire secretome present in conditioned cell culture supernatant, combined with a multiplex cytokine determination, we identified 998 proteins secreted by intrinsically aged NHDFs in culture. Seventy of these proteins exhibited an age-dependent secretion pattern and were accordingly denoted ‘skin aging-associated secreted proteins (SAASP)’. Systematic comparison of SAASP with the classical senescence-associated secretory phenotype (SASP) revealed that matrix degradation as well as proinflammatory processes are common aspects of both conditions. However, secretion of 27 proteins involved in the biological processes of ‘metabolism’ and ‘adherens junction interactions’ was unique for NHDFs isolated from intrinsically aged skin. In conclusion, fibroblasts isolated from intrinsically aged skin exhibit some, but not all, molecular hallmarks of cellular senescence. Most importantly, they secrete a unique pattern of proteins that is distinct from the canonical SASP and might reflect specific processes of skin aging.
Gesehen am 03.06.2020